China : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews macroeconomic developments in China in 1994 and 1995, in particular the progress achieved during these years in 'cooling' the economy following the intense overheating that originated in an investment boom in 1992. During 1994, efforts were intensified to achieve macroeconomic stability, with some initial headway being made in slowing the pace of economic activity. In 1995, demand and output further moderated toward more sustainable rates, with inflation declining steadily from the record high levels of 1994 to single-digit levels by end-1995.